Laminar Flow Induces Cell Polarity and Leads to Rearrangement of Proteoglycan Metabolism in Endothelial Cells - Grimm, Johannes; Keller, Ruprecht; Groot, Philip G de (Thrombosis and Haemostasis, 1988)
Bovine aortic endothelial cells in tissue culture were incubated with [35S]-sulfate to examine the pattern of proteoglycan production at various shear rates. It was observed that culturing bovine aortic endothelial cells under laminar flow changes the secretion pattern of proteoglycans to that observed in perfused organ cultures, induces polarity of secretion, down-regulates proteoglycan biosynthesis and decreases uptake of sulfate. These results indicate that surface shear is a major force influencing the endothelial cellular phenotype. The changed pattern of proteogly can release under static conditions may contribute to the anticoagulant effect of endothelial cells which is much needed when activated coagulation factors are not dispersed by flow.
Keywords: Proteoheparan sulfate; Heparan sulfate; Endothelial cells; Shear rate; Cell polarity